(untitled) (Journal of the College of Education for Women, 2023)
Topic management is the awareness of how speakers deal with initiating, developing, changing, and ending a topic and how they fix the relationship when a misunderstanding occurs. It is such an important unit of conversation as it includes the transition from one strategy to the other to be accomplished in a systematic and orderly manner. These strategies are impaired in dementia patients thus lead to communication breakdown. This study aims at detecting the dementia patients’ topic management strategies in selected speeches and answering the questions of which of these strategies are fully or partially detected in these speeches. The researchers use a qualitative method to examine the speeches of those patients and they adopt an eclectic model including the four strategies of topic management; they are: initiating of (Button & Casey, 1985), developing of (Leo & Thomas, 1998), changing of (Greatbach, 1986), and ending the topic of (Heydon, 2005). According to the findings of the study, patients with dementia are capable of developing conversational topics, but they are unable to initiate, change, or end the topics.